WAVE IN DECK ANALYSIS OF JACK UP PLATFORM MOPU DUE TO SUBSIDENCE - Yoga Randytama, Arief
As more offshore platforms reach its end life, subsidence became an increasingly important problem. Such phenomenon, which mainly occurs due to reservoir compaction, permits the occurence of wave in deck loading that became a notable concern in assessing the integrity of fixed offshore platforms. This study is focused on a jackup type Mobile Offshore Production Unit (MOPU) which consists of shell plated hull, tubular steel legs, and mudmat foundation. The generation of the finite element model comes naturally and is presented consisting of the detailed geomtery and mesh manipulation in order to obtain an acceptable model. Three scenarios are included in this study with concurently decreasing airgap and thus increasing the wave in deck inundation to the hull. Scenario 1 will not have any wave in deck occurence as it is assessed in positive airgap scenario, instead, the goal of scenario 1 is to propose steel strenghtening of the structure. Scenarios that involve wave in deck, i.e., scenario 2 and 3 were each subjected into different wave in deck loading calculation method. Wave in deck calculation method that are compared in this study is API, MSL, and BE method. Since BE method is only applicable when the bottom of steel of the hull is below still water level, which only occurs in scenario 3, scenario 2 will only compare API and MSL method while scenario 3 will compare all three. The comparison basis of different wave in deck methods in this thesis includes stress, vertical plate deflection, and stability analysis of the MOPU. The latter was examined in its bearing, sliding, and overturning capacity. Result shows that the MSL method consistently produce the most conservative result, followed by API and BE method. Additional conclusion include combination of the methods is necessary to yield a better result and represent accurate wave in deck phenomenon accordingly.